Chinese herbal medicine therapy and the risk of overall mortality for patients with liver cancer who underwent surgical resection in Taiwan. (December 2019) - Tsai, Fuu-Jen; Liu, Xiang; Chen, Chao-Jung; Li, Te-Mao; Chiou, Jian-Shiun; Chuang, Po-Heng; Ko, Cheng-Hang; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Liang, Wen-Miin; Lin, Ying-Ju
Highlights: We identified 1504 patients with liver cancer who underwent surgical resection. CHM users showed a significantly lower risk of overall mortality than non-users. Association rule mining and network analysis suggested that Bai-Hua-She-She-Cao, Ban-Zhi-Lian, and Suan-Zao-Ren were the most effective CHMs. Abstract: Liver cancer is the sixth most diagnosed cancer globally, and the second leading cause of cancer-related deaths. Surgical resection is a procedure performed to remove cancerous tissue from the liver. Chinese herbal medicine (CHM) is a complementary natural medicine system widely used for treatment of hepatic diseases in Asian countries. We investigated the effects on overall mortality of long-term use of CHM for treatment of patients with liver cancer who underwent surgical resection at the Taiwan Center for Medicine. We identified 1504 patients with liver cancer who underwent surgical resection. Of these patients, 210 CHM users and 210 non-users were selected, and were matched for age, gender, radiotherapy, and chemotherapy prior to CHM treatment. Chi-squared test, Cox proportional hazard modeling, the Kaplan-Meier method, log-rank test, association rule mining, and network analysis were used as statistical methods in this study. CHM users showed a significantly lower risk of overall mortality than non-users (HR: 0.57, 95% CI = 0.40-0.81; p = 0.0025; multivariate Cox proportional hazard model), and a lower 10-year cumulative incidence of overall mortality ( p < 0.05; log rank test). Association rule mining and network analysis suggested that Bai-Hua-She-She-Cao, Ban-Zhi-Lian, and Suan-Zao-Ren were the most effective CHMs. Therefore, we concluded that use of CHM as adjunctive therapy may reduce overall mortality in patients with liver cancer who underwent surgical resection. A list of herbal medicines with potential as future therapeutic interventions to prolong the life-span of patients with liver cancer who underwent surgical resection is also provided.